Burnout and Its Relationship With Depressive Symptoms in Medical Staff During the COVID-19 Epidemic in China - Huo, Lijuan; Zhou, Yongjie; Li, Shen; Ning, Yuping; Zeng, Lingyun; Liu, Zhengkui; Qian, Wei; Yang, Jiezhi; Zhou, Xin; Liu, Tiebang; Zhang, Xiang Yang (Frontiers in Psychology, 2021)
Objective The large-scale epidemic of Coronavirus Disease 2019 (COVID-19) has triggered unprecedented physical and psychological stress on health professionals. This study aimed to investigate the prevalence and risk factors of burnout syndrome, and the relationship between burnout and depressive symptoms among frontline medical staff during the COVID-19 epidemic in China. Methods A total of 606 frontline medical staff were recruited from 133 cities in China using a cross-sectional survey. The Maslach Burnout Inventory (MBI) was used to assess the level of burnout. Depressive symptoms were assessed by the Patient Health Questionnaire Depression (PHQ-9). Results During the COVID-19 pandemic, 36.5% of the medical staff experienced burnout. Personal and work-related factors were independently associated with burnout, including age (OR = 0.68, 95% CI: 0.52–0.89, p = 0.004), family income (OR = 0.72, 95% CI: 0.53–0.99, p = 0.045), having physical diseases (OR = 2.16, 95% CI: 1.42–3.28, p < 0.001), daily working hours (OR = 1.35, 95% CI: 1.03–1.77, p = 0.033), and profession of nurse (OR = 2.14, 95% CI: 1.12–4.10, p = 0.022). The correlation coefficients between the scores of each burnout subscale and the scores of depressive symptoms were 0.57 for emotional exhaustion, 0.37 for cynicism, and −0.41 for professional efficacy (all p < 0.001). Conclusions Our findings suggest that the prevalence rate of burnout is extremely high among medical staff during the COVID-19 pandemic, which is associated with other psychological disorders, such as depression. Psychological intervention for medical staff is urgently needed. Young and less experienced medical staff, especially nurses, should receive more attention when providing psychological assistance.